Table of Content - - (Journal of Islamic Sciences, 2025)
Table of Content: 1. The Sudanese Defensive Jihad Against the Rapid Support Forces (Rebels): A Comparative Jurisprudential Study with United Nations Law and the Universal Declaration of Human Rights Asst-Prof. Haith Balla Abdlla Salim 2. Treasure in the Light of the Holy Quran Ms. Hasna Hamid Thamer 3. Fundamentalist, jurisprudential, and intentional rules: types, differences between them, and their validity for deriving legal rulings Mr. Housin Mohammad Agah 4. Marital Disobedience: An Islamic Social Treatment Dr. Musatafa Muhammad Karakira